2014
DOI: 10.1080/15524256.2014.906370
|View full text |Cite
|
Sign up to set email alerts
|

Are Methadone Counselors Properly Equipped to Meet the Palliative Care Needs of Older Adults in Methadone Maintenance Treatment? Implications for Training

Abstract: Today's methadone patients differ greatly from those of the past. Because of the rise of polydrug use and the HIV and hepatitis epidemics, treatment has become much more complex, which multiply the concerns and complexities of treatment. Patients entering methadone programs are also more commonly presenting at ages well into their 50s, 60s, and 70s; and this phenomenon of high rates continues to grow. The majority of these individuals in treatment have presented with a number of significant comorbid medical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Most publications used ‘quality of life’ as a general term to encompass many facets of health and wellbeing (e.g. Doukas, 2014) [103]. Only one publication specifically operationalized quality of life, using subscales including overall social support, personal wellbeing, and satisfaction with life [104].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most publications used ‘quality of life’ as a general term to encompass many facets of health and wellbeing (e.g. Doukas, 2014) [103]. Only one publication specifically operationalized quality of life, using subscales including overall social support, personal wellbeing, and satisfaction with life [104].…”
Section: Resultsmentioning
confidence: 99%
“…Publication counts are not mutually exclusive, as publications could discuss multiple content areas. This diagram is simplified for the sake of visual clarity; additional levels of content area breakdown are provided in the Supporting information [103]. Only one publication specifically operationalized quality of life, using subscales including overall social support, personal wellbeing, and satisfaction with life [104].…”
Section: Bedi Et Al (2019) [48]mentioning
confidence: 99%
“…In the studies describing the diseases affecting this population, a great number of comorbidities were reported (Doukas, 2014;Gutiérrez-Cáceres et al, 2019;Hamilton & Grella, 2009;Searby et al, 2015), both physical, such as high blood pressure which was significantly greater in men than in women (Rosen et al, 2008), and mental problems, where 40% of those interviewed had dual pathology (Notley et al, 2015), depression being the most common diagnosis (Mortazavi et al, 2015), especially among women (Rosen et al, 2008).…”
Section: B) In Relation To Chronic Problemsmentioning
confidence: 99%
“…The articles showed that studies no longer solely examine population characteristics, prevalence, and mortality (Gutiérrez-Cáceres et al, 2019;Notley et al, 2015), but also the points of view of patients in treatment: their preferences regarding health care professionals (Conner et al, 2010), the type of treatment and levels of satisfaction with the latter, including the opinions of carers (Guo et al, 2010). Other studies recommended the use of a specific therapy, such as Problem-Solving Therapy, adapted as necessary to the specific needs of the study population , or envisaged future needs such as palliative care (Doukas, 2014).…”
Section: C) In Relation To Tackling Chronicitymentioning
confidence: 99%
See 1 more Smart Citation